Abnormal Distribution and Function of Circulating Monocytes and Enhanced Bacterial Translocation in Major Depressive Disorder - Alvarez-Mon, Miguel Angel; Gómez, Ana Maria; Orozco, Arancha; Lahera, Guillermo; Sosa, Maria Dolores; Diaz, David; Auba, Enrique; Albillos, Agustín; Monserrat, Jorge; Alvarez-Mon, Melchor (Frontiers in Psychiatry, 2019)
Introduction: Major depressive disorder (MDD) patients experience systemic inflammation. Monocytes play an important role in innate inflammatory responses and may be modulated by bacterial translocation. Our aim was to investigate the subset distribution and function of circulating monocytes, levels of proinflammatory cytokine, gut barrier damage and bacterial translocation in MDD patients. Methods: In this cross-sectional study, we recruited patients with MDD without any somatic or psychiatric comorbidities (n = 22), who were matched for sex, age, body mass index, race and smoking status to a non-depressed healthy control (HCs) group (n = 14). The levels of circulating CD14++CD16- (classical), CD14++CD16++ (intermediate) and CD14-CD16++ (nonclassical) monocytes and intracytoplasmic tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6 and IL-10 expression in the presence or absence of lipopolysaccharide (LPS) stimulation were analyzed by polychromatic flow cytometry. The serum TNF-α, IL-1β, IL-6 and IL-10 levels were measured by Luminex. LPS-binding protein (LBP), intestinal fatty acid-binding protein (I-FABP) and zonulin were measured by ELISA. Results: MDD patients had a significant increase in the frequency of intermediate monocytes and a significant decrease in the frequency of classical monocytes compared to those in the HC group. MDD patients had a significantly increased percentage of classical monocytes that expressed IL-1β, intermediate monocytes that expressed IL-1β and IL6 and nonclassical monocytes that expressed IL-1β, and decreased levels of nonclassical monocytes that expressed IL6 compared to those in the healthy controls. MDD patients had significantly increased levels of circulating TNF-α , IL-1β, LBP and I-FABP compared to those in the healthy controls. MDD patients with high LBP levels had a significant reduction in the number of circulating monocytes compared to that in the normal-LBP MDD patients, which can be mainly ascribed to a decrease in the number of intermediate and nonclassical monocytes. Conclusions: MDD patients showed a marked alteration in circulating monocytes, with an expansion of the intermediate subset with increased frequency of IL-1β and IL-6 producing cells as well as a systemic proinflammatory state, characterized by the enhanced serum TNF-α and IL-1β levels. Furthermore, MDD patients showed increased LBP and I-FABP levels, indicating increased bacterial translocation and gut barrier damage.